2015 Sea Art Festival : See- Sea & Seed - Dong-Lak LIM; Busan Biennale (Busan Biennale Organizing Committee, 2015)
Festival Catalog. Texts: Byung-Soo SUH, Dong-Lak LIM, Sung-Ho KIM, Seong-Hoon LIM.
English; Korean
Keywords: N4390-5098 Visual Arts- Exhibitions